2003
DOI: 10.1186/1477-3163-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The relationships of critical nutrients such as plant phenolics, vitamins, minerals and lipids are considered with respect to the incidence of a variety of cancers, and analyzed in terms of how these nutrient deficiencies alter immune function, DNA integrity and cell proliferation. With a significant correlation found between cancer and these nutrient deficiencies, the hypothesis is presented here that nutrition could provide a unifying perception of cancer and recast it as a single disease. This further sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Stress also down-regulates the digestive functions of the gut, including those of the stomach and pancreas. This in turn suppresses the uptake of critical nutrients that are essential for genomic stability [ 14 ]. It was reported that breast cancer patients as a group exhibit a depressed thyroid function [ 14 ], suggesting an etiological role for thyroid deficiency in neoplasia.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stress also down-regulates the digestive functions of the gut, including those of the stomach and pancreas. This in turn suppresses the uptake of critical nutrients that are essential for genomic stability [ 14 ]. It was reported that breast cancer patients as a group exhibit a depressed thyroid function [ 14 ], suggesting an etiological role for thyroid deficiency in neoplasia.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
“…This in turn suppresses the uptake of critical nutrients that are essential for genomic stability [ 14 ]. It was reported that breast cancer patients as a group exhibit a depressed thyroid function [ 14 ], suggesting an etiological role for thyroid deficiency in neoplasia. Thyroid function is profoundly affected by the iodine supply, and thyroid, breast and gastric cancers have been linked to iodine deficiency [ 14 ].…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemicelluloses have been reported to be used as a beater additive in papermaking4 and as a source of xylitol 5. They have also found potential use as food additives, thickeners, emulsifiers, and a cancer protective agents 6, 7. Xylose, a pentose sugar repeating unit of xylan, contains two easily accessible hydroxyl groups, offering various possibilities for chemical modifications, for example, benzylation,8 methacrylation,9 acetylation,2, 10 long‐chain acylation,11 and succinoylation 12, 13.…”
Section: Introductionmentioning
confidence: 99%